(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This article examines the role and importance of security of human in social philosophy. As safety of human in modern understanding appears one of the most important factors determining the consciousness and behavior of the individual and society. Reflects main aspects of security in the views of the philosophers in the context of the history of philosophy. Security in the modern understanding of the world is becoming one of the most important factors determining the consciousness and behavior of the individual and society. The emergence of various research approaches to the study of the phenomenon of security can be seen as an attempt to comprehend the dangers, threats, risks and challenges to human life and functioning of the family, society, state, civilization itself – as the basis for the phenomenon of security are historically different forms, types of socio-cultural activities to protect and promote individuals, social groups, family, society, state your goals, ideals, values and interests. Significance of the article is that it is very urgent for today’s Philosophical Science to learn in detail definitions of security. Keywords: security, philosophy, civil Society, valuables, danger, social cohesion, threat.